THE MEDIATION ROLE OF BEHAVIOR INTENTION IN ACTUAL USE OF SHOPEE BAROKAH - Nurkhasanah, Yeni (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2024)
The purpose of this study was to determine the impact of perceived usefulness, perceived ease of use and halal awareness on actual use of Shopee Barokah with behavior intention as a mediator. This research uses field research with a quantitative approach. Data was collected through distributing questionnaires. The population in this study were all gen z Muslim shopee users in Kudus Regency with sampling techniques using cochran formula, resulting in a total of 96 respondents. The test tool used in this research is the path analysis technique using the help of Smart-PLS 4 software. Based on the results of the channel analysis conducted, the results are obtained: (1) perceived usefulness has a positive impact on behavioral intention, (2) perceived ease of use has a positive impact on behavioral intention, (3) halal awareness has a positive impact on behavioral intention), (4) behavioral intention has a positive impact on actual use of Shopee Barokah among Gen Z in Kudus Regency, and (5) perceived usefulness, perceived ease of use, and halal awareness have a positive impact on actual use through the mediation of behavioral intention.